Atomic collisions in suprafluid helium-nanodroplets: timescales for metal-cluster formation derived from He-density functional theory. Issue 16 (28th April 2015) - Hauser, Andreas W.; Volk, Alexander; Thaler, Philipp; Ernst, Wolfgang E.
<x xml:space="preserve">Abstract</x> Two copper atoms, collected in a pickup-process by a He droplet consisting of 5000 atoms, move along rosetta-like, planar trajectories until the inter-particle attraction makes them collide.